Assessment of Accessibility and Quality of Emergency Obstetric Care services: A cross sectional study in rural Varanasi - Sarswat, Gauri Kumari; Sangeeta Kansal; Kumar, Alok; Joshua, Immanuel (Indian Journal of Community Health, 2021)
Background: Emergency Obstetrics care is an integrated strategy developed by the WHO, UNFPA and UNICEF that aims to equip health facilities with the capacity to provide evidence based, cost effective interventions to attend the leading causes of maternal mortality. Methods: A community based cross sectional study was conducted between April 2019 - July 2020. A total of 201 women who delivered in the last 6 months and had complications during their pregnancy were interviewed to find out accessibility and quality emergency obstetric Care (EmOC) services. Facility assessment was also done at two health facilities of Chiraigaon block for the assessment EmOC. Results: Findings show that only 41.8% respondents were able to reach the government health facilities in less than half-an-hour. Out of the total respondents who utilized government health facilities for EmOC, only 19% were attended by the health providers within 1 hour. Conclusion: Low percentage of respondents with complications were reaching the health facility within 30 minutes. Therefore, there is a strong need for strengthening of basic EmOC services at health facilities .